Aesthetic Values of Batak Toba Gondang Sadinding Music Performances at Gondang Sianjur Mula-mula Community - Yessica Yosia Virginia Simanjuntak; I Gede Yudarta (Institut Seni Indonesia Denpasar, 2023)
Gondang Sabangunan is one of a musical ensemble type that functions as an accompaniment to traditional ceremonies of the Toba Batak people. The Gondang Sabangunan performance by Gondang Sianjur Mula-Mula community has different form characteristics compared to other forms of Gondang. The performance of Gondang Sabangunan by Gondang Sianjur Mula-Mula community still maintains the use of original musical instruments amidst the rampant changes in the form of Gondang Sabangunan performances that use a mixture of modern musical instruments such as electric keyboard. The Gondang Sabangunan performance of the Gondang Sianjur Mula-Mula community is interesting to be studied more deeply to see the form and the aesthetic values of Gondang Sabangunan. This paper aims to find out the form and aesthetic value of Gondang Sabangunan. This article uses qualitative methods with an aesthetic approach The results of the discussion found that the form of three parts in the Gondang Sadinding performance related to traditional rituals, traditional ceremonies and social systems of the Batak people, while the aesthetic values found were pure values and extra aesthetic values based on Dalihan Na Tolu as the philosophy of kinship of the Batak community.